Design and Development of Microcontroller-Based Clinical Chemistry Analyser for Measurement of Various Blood Biochemistry Parameters. Issue 4 (11th December 2005) - Taneja, S. R.; Gupta, R. C.; Kumar, Jagdish; Thariyan, K. K.; Verma, Sanjeev
Abstract : Clinical chemistry analyser is a high-performance microcontroller-based photometric biochemical analyser to measure various blood biochemical parameters such as blood glucose, urea, protein, bilirubin, and so forth, and also to measure and observe enzyme growth occurred while performing the other biochemical tests such as ALT (alkaline amino transferase), amylase, AST (aspartate amino transferase), and so forth. These tests are of great significance in biochemistry and used for diagnostic purposes and classifying various disorders and diseases such as diabetes, liver malfunctioning, renal diseases, and so forth. An inexpensive clinical chemistry analyser developed by the authors is described in this paper. This is an open system in which any reagent kit available in the market can be used. The system is based on the principle of absorbance transmittance photometry. System design is based around 80C31 microcontroller with RAM, EPROM, and peripheral interface devices. The developed system incorporates light source, an optical module, interference filters of various wave lengths, peltier device for maintaining required temperature of the mixture in flow cell, peristaltic pump for sample aspiration, graphic LCD display for displaying blood parameters, patients test results and kinetic test graph, 40 columns mini thermal printer, and also 32-key keyboard for executing various functions. The lab tests conducted on the instrument include versatility of the analyzer, flexibility of the software, and treatment of sample. The prototype was tested and evaluated over 1000 blood samples successfully for seventeen blood parameters. Evaluation was carried out at Government Medical College and Hospital, the Department of Biochemistry. The test results were found to be comparable with other standard instruments.